Revisiting the principles of Gharar in Islamic banking financing instruments with special reference to Bay al-Inah and Bay al-Dayn towards a new modified model - Razali, Siti Salwani (2011)
One of the significant features of Islamic banking is the elimination of riba and gharar. However many problems arise in some of Islamic banking financing instruments when they are claimed to contain significant elements of gharar thus held unacceptable in certain Muslim countries. Among these instruments are Bay al-Inah and Bay al-Dayn. Currently, Bay al-Inah is not accepted in some countries such as the Middle East countries as it is regarded as part of interest-based transaction. However, in Malaysia, Bay al-Inah has been formalised as a permissible practice and is has emerged as the most important mode of transactions that stimulates the growth of Islamic transaction in Malaysia, which finally comes across the globe to be among the most successful Muslim state in the development Islamic Finance. On the other hand, Bay al-dayn or the sale of debt is not unanimously accepted or validated by Muslim scholars. Even though some scholars allow it in all forms and aspects, the others either disallow it entirely or allow it under certain circumstances and with certain clauses or conditions. This paper will discuss at length the concept of gharar or uncertainty and its occurrence in the contracts of Bay al Inah and Bay al Dayn. The paper will examine the definition of gharar theoretically including examples of the existence or occurrence of gharar in various types of contracts. Since the contracts of concern are Bay al Inah and Bay al Dayn specifically, the paper will discuss at length what each of these contracts is and how and where gharar is present in them. Subsequently, it details the legal implications of the presence of gharar on the validity of contracts in general and in Bay al Inah and Bay al Dayn contracts specifically. The opinions and views of major Muslim jurists on these matters are also highlighted. The paper will conclude with recommendations and suggestions on dealing with the issue of the existence of gharar in Bay al Inah and Bay al Dayn contracts hence making it feasible and acceptable to all muslim countries.